Investigação da ação da proteína anexina A1 sobre o processo de angiogênese induzido pelo fator de crescimento do endotélio vascular: modelos experimentais in vivo e in vitro - Lacerda, Jéssica Zani [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Introduction: The annexin A1 protein (ANXA1) is mainly involved in the regulation of inflammation, proliferative, growth and cell differentiation. Although these effects have been studied in several investigations, are scarce the studies in angiogenesis. The angiogenic therapy consists in the vascular growth control, and the discovery of ANXA1 protein action in this process result in the development of new therapeutic procedures. Aim: According to the importance of understanding the ANXA1 regulatory action in the new vessels formation, the objective of our research was to evaluate in vivo and in vitro, the action mechanism of this protein on angiogenesis, in the presence of the growth factor vascular endothelial - subtype A (VEGF-A). Methods: In vivo investigations have evaluated the ANXA1 effects on the kinetics of formation of new vessels of microcirculatory network of dorsal skin of BALB/c wild (WT) and ANXA1 depleted (AnxA1-/-) mice. In endothelial cells from human umbilical vein lineage (HUVEC) investigated the effect of ANXA1 on cell viability, proliferation, migration, tube formation, cell adhesion and molecules adhesion expression. Results: The WT animals treated with peptide ANXA12-26 (1 mg/kg) and VEGF and the AnxA1-/- animals treated with VEGF (10 ng/10 μL) show an increase of neovascularization in the skin. In HUVEC cells, the viability analysis does not show significant differences with ANXA12-26 at concentrations of 1, 10 and 30 μM. While, the cell proliferation increases with VEGF and/or ANXA12-26 treatments (1 μM). However, cell migration increases after ANXA12-26 treatment (10 μM) and, associated with VEGF, in concentrations of 10 and 30 μM. The tubulogenesis increases after induction with VEGF and does not change after ANXA12-26 treatment (1, 10 or 30 μM). In contrast, VEGF associated with ANXA12-26 (10 μM) enhance the formation of tubular structures. The ANXA12-26 peptide increases the expression of β3 integrin...

Introdução: A proteína anexina A1 (ANXA1) está envolvida principalmente na regulação dos processos inflamatórios, proliferativos, crescimento e diferenciação celular. Embora esses efeitos tenham sido explorados em diversas investigações, são raros os estudos na angiogênese. A terapia angiogênica consiste no controle do crescimento vascular, e a descoberta da ação da proteína ANXA1 nesse processo resultaria no desenvolvimento de novos procedimentos terapêuticos. Objetivo: em função da importância do entendimento da ação reguladora da ANXA1 na formação de novos vasos, o objetivo das nossas investigações foi avaliar, in vivo e in vitro, o mecanismo de ação dessa proteína sobre a angiogênese, na vigência do fator de crescimento do endotélio vascular - subtipo A (VEGF-A). Métodos: Nas investigações in vivo avaliamos os efeitos da ANXA1 sobre a cinética de formação de novos vasos da rede microcirculatória da região dorsal da pele de camundongos BALB/c selvagens (WT) e destituídos do gene para ANXA1 (AnxA1-/-). Na linhagem de células endoteliais de veias umbilicais humanas (HUVEC) investigamos o efeito da ANXA1 na viabilidade celular, proliferação, migração, formação de tubos, aderência e expressão de moléculas de adesão. Resultados: Os animais WT tratados com o peptídeo ANXA12-26 (1 mg/kg) ou VEGF e, os AnxA1-/- tratados com VEGF (10 ng/10 μL) apresentam aumento da neovascularização na pele. Nas células HUVEC, a análise da viabilidade não mostra diferenças significantes com ANXA12-26 nas concentrações de 1, 10 e 30 μM. Enquanto, a proliferação celular aumenta com o VEGF e/ou tratamento com ANXA12-26 (1 μM). No entanto, a migração celular aumenta após o tratamento com ANXA12-26 (10 μM) e, associado ao VEGF, nas concentrações de 10 e 30 μM. A tubulogênese aumenta após indução com VEGF e não altera após tratamento com ANXA12-26 (1, 10 ou 3...
Keywords: Genética; Proteínas angiogênicas; Neovascularização; Anexina; Substancias de crescimento; Endotelio vascular